2008
DOI: 10.1111/j.1600-0536.2008.01351.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity reactions associated with endovascular devices

Abstract: Allergic reactions to endoprostheses are uncommon and reported in association with orthopaedic, dental, endovascular and other implanted devices. Hypersensitivity reactions to the biomaterials used in endovascular prostheses are among the infrequent reactions that may lead to local or systemic complications following cardiovascular therapeutic interventions. This article reviews potential immunotoxic effects of commonly used biomaterials. Reports of putative hypersensitivity reactions to endovascular devices, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
115
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 78 publications
0
115
0
3
Order By: Relevance
“…Thyssen et al [109] performed an individual linkage study of 149 patients and found that nickel and/or chromium allergy in dermatitis patients does not appear to increase the overall risk of ISR after percutaneous coronary intervention. Honari et al [105] reached the same conclusion after an extensive review of the literature in 2008, namely, that studies performed until then often involve a limited number of patients and known risk factors (eg, stent length, reference diameter, patient characteristics including diabetes, and smoking) may confound the results. However, a recent meta-analysis of 9 studies by Gong et al [110] in 2013 (total of 1223 patients) arrived at the opposite conclusion, namely, having a pre-existing metal allergy increases the risk of ISR, with an odds ratio of 2.65.…”
Section: Intravascular Devicesmentioning
confidence: 72%
See 3 more Smart Citations
“…Thyssen et al [109] performed an individual linkage study of 149 patients and found that nickel and/or chromium allergy in dermatitis patients does not appear to increase the overall risk of ISR after percutaneous coronary intervention. Honari et al [105] reached the same conclusion after an extensive review of the literature in 2008, namely, that studies performed until then often involve a limited number of patients and known risk factors (eg, stent length, reference diameter, patient characteristics including diabetes, and smoking) may confound the results. However, a recent meta-analysis of 9 studies by Gong et al [110] in 2013 (total of 1223 patients) arrived at the opposite conclusion, namely, having a pre-existing metal allergy increases the risk of ISR, with an odds ratio of 2.65.…”
Section: Intravascular Devicesmentioning
confidence: 72%
“…With regards to DES in particular, Honari et al [105] noted that the existing data "suggest spectrums of hypersensitivity responses to DES," which include excessive inflammation, stent malposition, aneurysm formation, and late in-stent thrombosis. It is worth noting that hypersensitivity reactions to DES may be driven by factors other than the metal components, ie, the polymer.…”
Section: Intravascular Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…In individuals with Ni hypersensitivity, systemic allergic reactions to NiTi-based devices can cause inflammation near the implant and eventual device failure [3]. Biocompatibility concerns thus drive the development of low-Ni and Ni-free alternatives to conventional NiTibase SMAs.…”
Section: Introduction Motivation and Backgroundmentioning
confidence: 99%